Clarifying the effect of Cu element on the corrosion properties of Ni-Mo low alloy steel in marine environment. (15th May 2023) - Zhang, Tianyi; Liu, Wei; Dong, Baojun; Yang, Weijian; Chen, Longjun; Sun, Yipu; Li, Hai; Zhang, Bo
Abstract: Corrosion kinetics and rust layer protectiveness were combined to explore the effect of Cu content on the corrosion resistance of Ni-Mo low alloy steel in a simulated tropical marine atmospheric environment. The difference between the inner and outer rust layer protectiveness was discovered from the phase composition and distribution results and the evolution of electrochemical property. The synergistic effect of Cu with Ni and Mo on optimizing the rust layer protectiveness was revealed based on the formation and function of the appositional enrichment region (AER) inside the rust layer. Highlights: The synergistic effect of Cu, Ni and Mo on improving the rust layer protectiveness was comprehensively illustrated. Cu promoted the generation of CuFeO2 and the formation appositional enrichment region of Cu, Ni and Mo. The difference of protectiveness between the inside and outside rust layer was confirmed.